Distance Protection Using Fuzzy Logic - علي بتول (Latakia University Journal -Engineering Sciences Series, 2024)
When there is a malfunction, the protection is sensitive to the malfunction. If the disconnection command is sent instantaneously, it is possible to disconnect the transmission line without a malfunction requiring disconnection. Another way to give an unconsidered time limit may lead to the malfunction continuing for a long enough period to cause damage to the equipment, so it must be determined. The exact value of the fault current that must be detected by the protection, in addition to the appropriate choice of time delay depending on the type of fault. All of these questions were the reason for our choice of fuzzy logic in controlling this protection to study the effect of this control on the performance of the protection, as some references suggest the presence of a time delay between 0 and 4.5 seconds depending on the type of fault.